Missense dopamine transporter mutations associate with adult parkinsonism and ADHD - Freja H. Hansen; Tina Skjørringe; Saiqa Yasmeen; Natascha V. Arends; Michelle A. Sahai; Kevin Erreger; Thorvald F. Andreassen; Marion Holy; Peter J. Hamilton; Viruna Neergheen; Merete Karlsborg; Amy H. Newman; et al. (The Journal of Clinical Investigation, 2014)
Parkinsonism and attention deficit hyperactivity disorder (ADHD) are widespread brain disorders that involve disturbances of dopaminergic signaling. The sodium-coupled dopamine transporter (DAT) controls dopamine homeostasis, but its contribution to disease remains poorly understood. Here, we analyzed a cohort of patients with atypical movement disorder and identified 2 DAT coding variants, DAT-Ile312Phe and a presumed de novo mutant DAT-Asp421Asn, in an adult male with early-onset parkinsonism and ADHD. According to DAT single-photon emission computed tomography (DAT-SPECT) scans and a fluoro-deoxy-glucose-PET/MRI (FDG-PET/MRI) scan, the patient suffered from progressive dopaminergic neurodegeneration. In heterologous cells, both DAT variants exhibited markedly reduced dopamine uptake capacity but preserved membrane targeting, consistent with impaired catalytic activity. Computational simulations and uptake experiments suggested that the disrupted function of the DAT-Asp421Asn mutant is the result of compromised sodium binding, in agreement with Asp421 coordinating sodium at the second sodium site. For DAT-Asp421Asn, substrate efflux experiments revealed a constitutive, anomalous efflux of dopamine, and electrophysiological analyses identified a large cation leak that might further perturb dopaminergic neurotransmission. Our results link specific DAT missense mutations to neurodegenerative early-onset parkinsonism. Moreover, the neuropsychiatric comorbidity provides additional support for the idea that DAT missense mutations are an ADHD risk factor and suggests that complex DAT genotype and phenotype correlations contribute to different dopaminergic pathologies.